Raman and Dielectric Studies on Lead free (K0.5Na0.5) NbO3 Piezoelectric Ceramics. Issue 1 (17th February 2015) - Mahesh, P; Pamu, D
Abstract: The present study demonstrates the preparation of (K0.5 Na0.5 )NbO3 (KNN) ceramics at low temperatures by using mechanochemical synthesis process. The effect of calcination temperature on structure, and dielectric properties of KNN ceramics have been studied systematically. It is found that both the dielectric constant and tanδ of KNN ceramics as a function of temperature exhibited two sharp phase transitions indicating orthorhombic to tetragonal (184°C) and ferroelectric tetragonal to paraelectric cubic phases (385°C). It was observed that the ceramics calcined at 700°C and sintered at 1000°C shows the high Curie temperature, high dielectric permittivity and low dielectric loss. Further with increase in calcination temperature, the ferroelectric tetragonal to paraelectric cubic phase shifted to lower temperatures. Raman spectra of KNN ceramics were obtained and the three characteristic Raman peaks in the spectra of KNN are related to the internal vibrations of the NbO6 octahedron. The effect of processing parameters on dielectric properties and phase transitions studied systematically.